A charge sharing–based switching scheme for SAR ADCs. (29th April 2019) - Akbari, Meysam; Hashemipour, Omid; Nazari, Masoud; Moradi, Farshad
Summary: This paper presents an energy‐efficient switching scheme for successive approximation register (SAR) analogue‐to‐digital converter (ADC). The proposed scheme employs charge recycling method to keep the capacitor arrays free of transitional energy between bit generations except reset phase. In comparison with the conventional switching scheme, the proposed one achieves 100% transitional energy saving without considering reset phase. In addition, configuration of a 10‐bit SAR ADC shows that the proposed switching scheme reduces the capacitor area by 25% compared with the conventional switching scheme. Abstract : This paper presents a new switching scheme for SAR ADCs based on the charge recycling method, which leads to a zero‐energy consumption during conversion phase. In addition, configuration of a 10‐bit SAR ADC shows that the proposed scheme results in a 25% reduction in the capacitor area.